GART Functions as a Novel Methyltransferase in the RUVBL1/β‐Catenin Signaling Pathway to Promote Tumor Stemness in Colorectal Cancer - Chao Tang; Mengying Ke; Xichao Yu; Shanliang Sun; Xian Luo; Xin Liu; Yanyan Zhou; Ze Wang; Xing Cui; Chunyan Gu; Ye Yang (Advanced Science, 2023)
Abstract Tumor stemness is associated with the recurrence and incurability of colorectal cancer (CRC), which lacks effective therapeutic targets and drugs. Glycinamide ribonucleotide transformylase (GART) fulfills an important role in numerous types of malignancies. The present study aims to identify the underlying mechanism through which GART may promote CRC stemness, as to developing novel therapeutic methods. An elevated level of GART is associated with poor outcomes in CRC patients and promotes the proliferation and migration of CRC cells. CD133+ cells with increased GART expression possess higher tumorigenic and proliferative capabilities both in vitro and in vivo. GART is identified to have a novel methyltransferase function, whose enzymatic activity center is located at the E948 site. GART also enhances the stability of RuvB‐like AAA ATPase 1 (RUVBL1) through methylating its K7 site, which consequently aberrantly activates the Wnt/β‐catenin signaling pathway to induce tumor stemness. Pemetrexed (PEM), a compound targeting GART, combined with other chemotherapy drugs greatly suppresses tumor growth both in a PDX model and in CRC patients. The present study demonstrates a novel methyltransferase function of GART and the role of the GART/RUVBL1/β‐catenin signaling axis in promoting CRC stemness. PEM may be a promising therapeutic agent for the treatment of CRC.